VỀ NGHIÊN CỨU CÁC PHỨC HỆ ĐÁ HỖN HỢP (OLISTOSTROM, MICTIT) Ở VIỆT NAM - Bách, Lê Duy; Nghi, Trần; Thắng, Ngô Gia (Vietnam Journal of Earth Sciences, 2017)
The investigation of mictite rock complexes iswidely carrying out in the folded belts around the wolrd. These rock complexes have different agesfrom Precambrian up to Cenozoic and different sources and ongrn. The most common charactaristics of them is that for all the origin they have to pass through two groups of proccesses: the group of formation of classical materials and the group of material transport from the sources into the depositional places. The rock complexes may have been classified by the types of their origin, basing on their formation procceses.In Vietnam these rock complexes have been investigated by the authors in the Northeast, Northwest, Truongson and the West Nambo folded regions for the first time. They are the indicative rock complexes for the lateral and vertical tectonic movements being existed in tectonic history of lithosphere.